Batimetria e análise espacial de macrobentônicos dos Recifes do Seixas, João Pessoa, Paraíba, Brasil - Lima, Raoni da Costa (2017)
The Seixas reef has become, in recent years, one of the most important tourist attractions in João Pessoa, due to the commercial exploitation of tourism. However, there is no initiative in the Seixas reef and there wasn’t registered any action with aim to regulate the commercial activity in the area, until the year of this work, since it is just like other ones in place, like fishing and materials extraction, related to environmental impacts. The Seixas reef has a fundamental ecological importance, because it supports benthic species and a whole network of interactions related to them, in addition, reef preservation is fundamental to mitigate erosive processes on adjacent beaches. In this sense, aiming to promote a deepening knowledge of the area and encourage activities that can preserve it, a bathymetric mapping of the reef body was developed which revealed a rather complex shape with decreasing average altimetry from east to west. In addition to bathymetry were developed spatial maps of the dominant macroalgae in coverage, based on georeferenced quadrants which evidenced trends in the distribution of species related to landscape elements, such as bathymetry itself.